The Effect of Health Education on Atypical Progressive Acute Kidney Disorder (GGAPA) on Parents' Anxiety Levels - Ramaita, Ramaita; Ajani, Anggra Trisna; Yuderna, Vivi; Asman, Aulia; Putri, Triyana Harlia; Handayani, Reska (Indonesian Journal of Global Health Research, 2024)
Cases of atypical acute kidney disorder have afflicted 269 children with a high percentage of death or fatality rate reaching 58 percent or as many as 157 children from August to October 2022. A total of 189 cases have been reported, most of which are dominated by children aged 1–5 years. This incident causes serious anxiety in the community, especially parents who have children under five One technique to reduce anxiety is to provide health education. This study aims to better understand the effect of Health Education on the typical symptoms of atypical progressive acute kidney disorder (GGAPA) in children and its anticipation of the anxiety level of parents who have toddlers in the Sungai sariak health center work area in 2023. This type of research is quasi-experimental, using one group pretest-posttest design The research sample is parents who have toddlers totaling 35 people taken through Purposive sampling techniques. The study was conducted from July 14 to August 31, 2023. Information was collected using the Hamilton Anxiety Rating Scale (HARS) and analyzed using a paired sample t-test. The results of the analysis showed that the average level of anxiety in the first measurement (before Health Education was given) was 3.03 with a standard deviation of 0.985 In the second measurement, the average anxiety level of parents who have toddlers was 1.23 with a standard deviation of 1.239. The results of the statistical test obtained a value of 0.000, it can be concluded that there is a significant difference between the level of anxiety of the first measurement, namely before Health Education about the typical symptoms of Atypical Progressive Acute Kidney Disorder (GGAPA) and the second, namely after being given Health Education.